Flexibility and strength in brazilian and portuguese gymnasts - Amanda Batista; Rui Garganta; Lurdes Ávila-Carvalho (Asociación Española de Ciencias del Deporte, 2019)
Introduction: The purpose of this study was: 1) compare the flexibility and strength levels and 2) investigate possible functional asymmetries in flexibility in gymnasts from two National Teams of Rhythmic Gymnastics. Material and Methods: Participants included nine gymnasts from Brazilian National Team (BNT) (20.8±1.9 years) and four gymnasts from Portuguese National Team (PNT) (15.8±1.3 years). Ten specific flexibility tests and six specific strength tests were used. The Mann-Whitney and Wilcoxon tests were applied. Results and Conclusions: The Brazilian National Team was composed by older gymnasts with more years of practice than Portuguese National Team. The groups obtained similar training volume. Brazilian  gymnasts showed an advantage in all strength tests, although significant differences were observed in 66.7% of tests. On the other hand, the Portuguese gymnasts reached higher results than Brazilian gymnasts in the spine and shoulders flexibility, although without statistical significance, as well as lower levels of functional asymmetries. In the lower limbs flexibility, the groups showed excellent results with preferred lower limb. However, functional asymmetries in the flexibility tests were found in 88.9% and 50% of Brazilian and Portuguese gymnasts, respectively. Therefore, we cannot observe an absolute superiority of one National Team in the motor performance.